The greatest skating race : a World War II Story from the Netherlands - Borden, Louise (Margaret K. McElderry Books, 2004)
During World War II in the Netherlands, a ten-year-old boy's dream of skating in a famous race allows him to help two children escape to Belgium by ice skating past German soldiers and other enemies.